Pelatihan Penggunaan Mendeley dalam Pembuatan Karya Ilmiah untuk Meningkatkan Keterampilan Menulis Calon Guru - Kurniawan, Ade; Sanapiah, Sanapiah; Syahrir, Syahrir; Masjudin, Masjudin; Permata, Reny Amalia; Abidin, Zainal (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2026)
Training on the use of Mendeley in creating scientific papers aims to improve scientific writing skills among prospective teachers, especially in terms of managing references and citations in accordance with academic standards. This activity was carried out online with 29 participants from the Faculty of Science, Engineering, and Applied Sciences, Mandalika University of Education. This community service method adopted a practice-based training approach. The training involved two main sessions, namely a theory session and a practice session. In the theory session, participants were given an understanding of the importance of scientific writing in accordance with academic standards and how to use Mendeley in reference management. The practice session focused on teaching the use of Mendeley directly, from installing the application to managing references and inserting automatic citations in documents. Evaluation was carried out through pre-tests and post-tests to measure the improvement of participants' skills. The evaluation results showed a significant improvement in participants' skills. Before the training, only 30% of participants were able to operate Mendeley properly, but after the training, 92% showed significant improvement. The training also accelerated the process of compiling a reference list, from 3-4 hours to just 15-30 minutes. This training is expected to improve the quality of scientific writing among student teachers and prepare them to produce more structured, efficient, and academically compliant scientific work.